A new sequential treatment strategy for multiple colorectal liver metastases: Planned incomplete resection and postoperative completion ablation for intentionally-untreated tumors under guidance of cross-sectional imaging. Issue 2 (February 2021) - Okuno, Masayuki; Kawaguchi, Yoshikuni; De Bellis, Mario; Vega, Eduardo A.; Huang, Steven Y.; Ahrar, Kamran; Gupta, Sanjay; Vauthey, Jean-Nicolas; Odisio, Bruno C.
Abstract: Purpose: We retrospectively evaluated outcomes of a new sequential treatment strategy for patients with multiple colorectal liver metastases (CLM): planned incomplete resection and postoperative percutaneous completion ablation for intentionally-untreated lesions under cross-sectional imaging guidance. Methods: Patients with CLM who underwent curative-intent hepatectomy and ablation during 2007–2018 were analyzed. Complications, local tumor progression (LTP) rates at ablation site(s), and overall survival (OS) estimated using the Kaplan-Meier method were compared between patients who underwent CLM resection and postoperative percutaneous ablation for intentionally-untreated lesions (completion ablation) and patients who underwent CLM resection and concomitant intraoperative CLM ablation under ultrasound guidance. Results: Number and largest diameter of CLM and liver resection complexity did not differ significantly between the completion ablation (n = 23) and intraoperative ablation (n = 92) groups. Microwave (versus radiofrequency) ablation was used more frequently in the completion ablation group than in the intraoperative ablation group (61% [14/23] vs. 6% [6/92], P = 0.001). The complication rate after hepatectomy and ablation was significantly lower in the completion ablation group (21% [5/23] versus 48% [44/92], P = 0.033). No death was observed in either group. The 5-year LTP cumulative incidence was significantly lower in the completion ablation group (31.7% versus 62.4%, P = 0.030). The 5-year OS rate did not differ significantly between groups (53%, completion ablation; 42%, intraoperative ablation; P = 0.407). Conclusions: Resection and postoperative percutaneous completion ablation under cross-sectional imaging guidance may be a safe and effective treatment pathway in patients with CLM in whom liver resection alone cannot achieve R0 resection. Highlights: - R0 resection is challenging in patients with extensive colorectal liver metastasis - Surgery in combination ablation has been applied with the intent of achieving R0. - Planned completion ablation after hepatectomy is a new treatment strategy. - This new strategy was associated with lower complication and recurrence rates.